Cannabis Use and Dependence among French Schizophrenic Inpatients - Lejoyeux, Michel; Basquin, Anne; Koch, Marie; Embouazza, Houcine; Chalvin, Florence; Ilongo, Michaelle (Frontiers in Psychiatry, 2014)
Background: To assess the prevalence of cannabis use and dependence in a population of schizophrenic inpatients and to compare schizophrenics with and without cannabis consumption. Methods: 101 schizophrenic patients were examined during their first week of hospitalization. They answered the PANNS scale of schizophrenia, the CAGE and the Fagerström questionnaire and the DSM-IV-TR criteria for cannabis, alcohol, opiates and nicotine use dependence were checked. We also assessed socio-demographic characteristics, the motive of cannabis consumption and the number of cannabis joints and alcoholic drinks taken. Results: The prevalence of cannabis consumption was 33.6% among schizophrenic inpatients. Schizophrenics consuming cannabis were younger than non-schizophrenics (33.3 vs 44.7 years p< 0.0001), more often male (77 % vs 54%, p=0.02) and had been hospitalized for the first time in psychiatry earlier (24.3 vs 31.3 p=0.003). 88 % of cannabis consumers were dependent on cannabis. They were more often dependent on opiates (17% vs 0%) and alcohol (32 % vs 7.4%, p=0.001) and presented compulsive buying more often (48% vs 27 %, p=0.04). Factor analysis revealed that factors associated to cannabis consumption among schizophrenics were cannabis dependence, male gender, pathological gambling, opiate dependence, number of joints smoked each day and compulsive buying. Conclusion: 33.6 % of the schizophrenic patients hospitalized in psychiatry consume cannabis and most of them are dependent on cannabis and alcohol. Hospitalization in psychiatry may provide an opportunity to systematically identify a dependence disorder and to offer appropriate information and treatment